2021
DOI: 10.1111/brv.12797
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of microglia

Abstract: Microglial cells are the scions of foetal macrophages which invade the neural tube early during embryogenesis. The nervous tissue environment instigates the phenotypic metamorphosis of foetal macrophages into idiosyncratic surveilling microglia, which are generally characterised by a small cell body and highly ramified motile processes that constantly scan the nervous tissue for signs of changes in homeostasis and allow microglia to perform crucial homeostatic functions. The surveilling microglial phenotype is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 343 publications
(463 reference statements)
0
56
0
Order By: Relevance
“…However, at both transcriptional and functional levels, microglia appear to be more complex and dynamic than anticipated. This might explain why engagement of microglia can be either neuroprotective or neurotoxic, leading to attenuation or exacerbation of disease progression ( 10 , 15 , 136 ) depending on the context. According to the traditional classification of macrophages/microglia, during microglial activation following an inflammatory insult, cell morphology is altered either to M1, the typically activated phenotype, or to M2, an alternative activated phenotype; and this phenotypic switch depends on the type of insult.…”
Section: Pro-inflammatory Pathways In Microgliamentioning
confidence: 99%
See 1 more Smart Citation
“…However, at both transcriptional and functional levels, microglia appear to be more complex and dynamic than anticipated. This might explain why engagement of microglia can be either neuroprotective or neurotoxic, leading to attenuation or exacerbation of disease progression ( 10 , 15 , 136 ) depending on the context. According to the traditional classification of macrophages/microglia, during microglial activation following an inflammatory insult, cell morphology is altered either to M1, the typically activated phenotype, or to M2, an alternative activated phenotype; and this phenotypic switch depends on the type of insult.…”
Section: Pro-inflammatory Pathways In Microgliamentioning
confidence: 99%
“…It has been shown that INF is a canonical cytokine that can polarize microglia toward M1. It is noteworthy that the classification of the M1 and M2 phenotypes have been challenged ( 10 , 136 , 137 ). The reason is that such classification has been defined mainly based on in vitro studies of peripheral macrophages and that M1 and M2 states fail to emerge in brain resident microglia.…”
Section: Pro-inflammatory Pathways In Microgliamentioning
confidence: 99%
“…2 B). Through the expression of known markers expressed by some specific hypothalamic cell clusters [ 42 46 ], we determined the cell type represented by each cluster; that is, clusters 0, 1, 3, 5, 8, and 9 were neurons (snap25+/syt1+), clusters 7, 11, and 15 were microglia (csf1r+/cx3cr1+), clusters 4 and 13 were astrocytes (agt+), clusters 2 and 10 were oligodendrocyte glial cells (cldn11+), cluster 6 was oligodendrocyte precursor cells (pdgfra+/olig1+), cluster 12 was tanycytes (rax+/crym+), cluster 16 was dural cells (mgp+), and cluster 14 was pia mater cells (lum+) (Fig. 2 C).…”
Section: Resultsmentioning
confidence: 99%
“…After removing the mitochondrial genes from all the cells through an unsupervised strategy, clustering was performed, and 16 populations were found. Through the expression of markers expressed by some specific cell clusters [ 42 46 ], we determined the cell type represented by each cluster and identified a large number of glial cells, including microglia (Additional file 4 : Fig. S4C).…”
Section: Resultsmentioning
confidence: 99%
“…Glial cells can also participate in neuronal migration, potentially contributing to the development of CZS. Although microglial cells can adopt the inflammatory phenotype to exert neuroprotective functions ( Augusto-Oliveira et al, 2021 ), their persistent activation can be associated with chronic neuroinflammation. This potential event can link Zika infection both to microcephaly and to neurodegenerative/neuropsychiatric diseases in adults ( Beys-da-Silva et al, 2020 ).…”
Section: Mechanisms: Lessons From Experimental Studiesmentioning
confidence: 99%